An examination of works for wind band, brass ensemble and percussion ensemble: “Suite Française” by Darius Milhaud, “Hats Off to Thee” by John Zdechlik and “Mercury Rising” by Nathan Daughtrey - Bernard-Stevens, Sarah Anne (Kansas State University, 2012)
The following report contains the research and analysis of three musical compositions prepared for effective rehearsal and performance for the Graduate Conducting Recital. The repertoire selected includes Hats Off to Thee by John Zdechlik, performed by the Kansas State University Brass Ensemble on April 18th, 2012; Mercury Rising by Nathan Daughtrey, performed by the Kansas State University Percussion Ensemble on April 3rd, 2012 and Suite Française by Darius Milhaud, performed by the Kansas State University Concert Band on April 25th, 2012 all under the direction of Sarah Bernard-Stevens. The report comprises extensive research and theoretical analysis compiled to effectively rehearse and conduct the above-mentioned works.
Keywords: Wind Band; Conducting; Suite Francaise; Music (0413)